2016
DOI: 10.7324/jabb.2016.40609
|View full text |Cite
|
Sign up to set email alerts
|

Precision Farming: The Future of Indian Agriculture

Abstract: Precision Farming or Precision Agriculture is generally defined as information and technology based farm management system to identify, analyse and manage spatial and temporal variability within fields for optimum productivity and profitability, sustainability and protection of the land resource by minimizing the production costs. Increasing environmental consciousness of the general public is necessitating us to modify agricultural management practices for sustainable conservation of natural resources such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 7 publications
0
16
0
3
Order By: Relevance
“…It is a holistic approach that helps the farmer to manage the spatial and temporal variability within the field for agriculture revolutionization by increasing the profitability, optimizing yield and quality, and reducing cost (Paustian and Theuvsen, 2017) and is regarded as a paradigm shift in the management of spatial and temporal variability of soil and crop within the agricultural sector (Whelan and Mcbratney, 2000). Precision farming is an appealing concept (Hakkim et al, 2016) which identifies the controllable yield-limiting factors and determines variability by using modern technologies such as geographical information system (GPS), remote sensing (RS) and geographical positioning system (GPS) (Tripathi et al, 2013) (Table 2). The ability to locate the precision position in the farm helps to create the map of spatial and temporal variability of the variables such as crop yield, soil moisture level, organic matter content, nitrogen level, pH, topography, etc.…”
Section: Conceptual Framework Of Precision Agriculturementioning
confidence: 99%
See 3 more Smart Citations
“…It is a holistic approach that helps the farmer to manage the spatial and temporal variability within the field for agriculture revolutionization by increasing the profitability, optimizing yield and quality, and reducing cost (Paustian and Theuvsen, 2017) and is regarded as a paradigm shift in the management of spatial and temporal variability of soil and crop within the agricultural sector (Whelan and Mcbratney, 2000). Precision farming is an appealing concept (Hakkim et al, 2016) which identifies the controllable yield-limiting factors and determines variability by using modern technologies such as geographical information system (GPS), remote sensing (RS) and geographical positioning system (GPS) (Tripathi et al, 2013) (Table 2). The ability to locate the precision position in the farm helps to create the map of spatial and temporal variability of the variables such as crop yield, soil moisture level, organic matter content, nitrogen level, pH, topography, etc.…”
Section: Conceptual Framework Of Precision Agriculturementioning
confidence: 99%
“…Data from satellites, GPS, GIS, remote sensors provide a better understanding of the spatial and temporal variability within the field to the farmers. Farmers can, therefore, precisely manage inputs and production factors such as seed, water, fertilizers, labor, pesticides for increasing yield and efficiency (Hakkim et al, 2016).…”
Section: Crop Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcome was a drastic reduction in cost and improved quality agricultural production and precision irrigation on combining applications of precision agriculture and WSN. Hakkim et al [29], concluded that an increase economic returns as well as reduce the energy input and environmental impacts of agriculture through precision farming. Tools and equipment used were Global Positioning System (GPS), sensor technologies, geographic information system (GIS), grid soil sampling and variable-rate fertilizer (VRT) application, crop management, soil and plant sensors, rate controllers, precision irrigation and in pressurized systems, software, yield monitor and precision farming on arable land, precision farming within the fruits, vegetables and viticulture sectors.…”
Section: Maximize the Outputmentioning
confidence: 99%